1962
DOI: 10.1530/acta.0.0400493
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Histology in Patients With Male Pseudohermaphroditism and Atypical Gonadal Dysgenesis: Relation to Theories of Sex Differentiation

Abstract: The anatomic findings and gonadal histology of 41 patients who had atypical forms of gonadal dysgenesis or of male pseudohermaphroditism are described. Fourteen of these cases were classified as atypical gonadal dysgenesis because there were gross evidences of abnormal gonadal development, differing from those of classical Turner's syndrome. In this group there was no incidence of familial inheritance but there were evidences of chromosomal aberrations. Two patients diagnosed as [00BB]gonadal dysplasia[00AB] h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1964
1964
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…It is now well established, for example, that patients with asymmetric gonadal differentiation frequently have a 45,X/46,XY mosaicism [Bergadá and Cleveland, 1962;Josso et al, 1966] or that the presence of a 46,XX cell line and ovotestes are the most frequent findings in ovotesticular DSD [Verkauskas et al, 2007]. However, in his usual practice the physician is confronted with a patient in whom he finds signs or symptoms, from which he has to draw conclusions in order to approach a diagnosis and take an action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now well established, for example, that patients with asymmetric gonadal differentiation frequently have a 45,X/46,XY mosaicism [Bergadá and Cleveland, 1962;Josso et al, 1966] or that the presence of a 46,XX cell line and ovotestes are the most frequent findings in ovotesticular DSD [Verkauskas et al, 2007]. However, in his usual practice the physician is confronted with a patient in whom he finds signs or symptoms, from which he has to draw conclusions in order to approach a diagnosis and take an action.…”
Section: Discussionmentioning
confidence: 99%
“…A vast majority of these patients (86%) had asymmetric gonadal differentia-tion -also known as mixed gonadal dysgenesis and included in the sex chromosome DSD of the recently proposed nomenclature -but the mosaicism was also found in patients with 2 dysgenetic testes. Asymmetric gonadal differentiation was first described in patients with a 45,X/46,XY mosaicism [Bergadá and Cleveland, 1962], and it was believed for years that the sole existence of this abnormal karyotype would be associated with abnormal gonadal differentiation. However, the increasing practice of prenatal karyotyping has shown that a 45,X/46,XY mosaicism can be an accidental finding in a boy with normal genitalia [Telvi et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sohval [3] the condition is classified as mixed gonadal dysgenesis, corresponding to the term asym m etrical gonadal differentiation, as named by Bergada et al [1]. Both term s indicate th a t these patients form a transient group from pure gonadal dysgenesis to male pseudohermaphoroditism with bi lateral testicular developm ent.…”
mentioning
confidence: 99%
“…[10] and Greenblatt [9]. 8 cases were reported by Bergada et al [2]. Recently Sohval in his excellent reviews [19,20] delineated such cases as a special type of intersexuality and proposed the name of " mixed" gonadal dys genesis.…”
mentioning
confidence: 99%